Making a Website Using HTML and CSS for SMK Student - Muhammad Annafri; Arif Bijaksana Putra Negara; Heri Priyanto; Yulianti; Helen Sasty Pratiwi; Niken Candraningrum (Tanjungpura International Journal on Dynamics Economics, Social Sciences and Agribusiness, 2023)
In today's digital era, one of the education that is taught a lot is about the website, a means to get information. In making a fundamental web, there are 4 important that must be mastered including Hyper Text Markup Language (HTML), Cascade Style Sheets (CSS), Hypertext Preprocessor programming language (PHP) and database management system / DBMS (MySQL). HTML and CSS have a close relationship where HTML is a markup language (site foundation) and CSS fixes style (for all aspects related to the appearance of the website) so that these two programming languages ​​must go hand in hand. SMK N 1 Sungai Raya Kepulauan, is one of the favorite SMKs in the Sungai Raya Kepulauan region where the expertise programs possessed are mostly knowledge related to technology, namely Computer and Network Engineering (TKJ) and Software Engineering (RPL) so that students requires in-depth knowledge of technology, especially in terms of Web Programming so that this knowledge can be useful for students in the world of work.